Implikatur Percakapan Dengan Unsur Penolakan Pada Drama Jepang Dear Sister - Fitri Fauziyyah (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2024)
This research is to find out about the implicature with elements of rejection in the Japanese drama Dear Sister. The problems in this research are about the implied meaning of the rejection speech contained in the Japanese drama Dear Sister and classify the types of implicature in the Japanese drama Dear Sister using Grice's theory. This research is descriptive with qualitative approach. The methods used in this analysis are listening and note-taking methods. The data source used in this research is the Japanese drama series Dear Sister with a total of 10 episodes. From the results, 20 data were found with 8 meanings of rejection, namely the meaning of rejection of offers, gifts, orders, requests or requests, statements, invitations, suggestions, and praise. As for the results of the 20 data that the author has examined, the type of implicature that often appears is the conventional type of implicature, with the results of the conventional type of implicature as much as 14 data, while the unconventional type of implicature is 6 data. In this study, the data with the type of nonconventional implicature also contained violation of the maxim of relevance, violation of the maxim of manner, violation of the maxim of quality, compliance with the maxim of relevance, and compliance with the maxim of quality.